ROOTING RESPONSE OF ROSEMARY AND LAVENDER CUTTINGS TO YARD TRIMMING COMPOST, MANURE AND HUSK AS SUBSTRATES IN NURSERY MEDIUM - Tavakol, T.; Hoseinzadeh, P. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Propagation from cuttings is the commonest vegetative method. The rooting medium conditions can affect the rooting percentage and speed significantly. Most biological processes are speeded up when temperatures are higher and so raising compost temperature usually increases the rapidity with which cuttings root. Bottom heat systems are prepared to stimulate rooting speed and diminish the rooting period of the transplanted cuttings. Considering the energy consumption in bottom heat systems, implementation of yard trimming compost, manure and husk as the substrate of medium in order to simulate the effects of bottom heat systems and surveying its impacts on rooting of two medicinal plants (Rosmarinus officinalis L. and Lavandula officinalis L.), were evaluated. The cuttings were collected and transplanted during February 2008. Rooting percentage, rooting speed, root dry matter and leaf number were assessed. Results presented higher rooting percentage and leaf number as well as rooting speed and root dry matter in cuttings which were treated with yard trimming compost substrate compared to other treatments and control. Husk substrate had the least effect on the mentioned characteristics.